Exploration of High-Grade Transformation and Postoperative Radiotherapy on Prognostic Analysis for Primary Adenoid Cystic Carcinoma of the Head and Neck - Zhu, Yuelu; Zhu, Xinyi; Xue, Xuemin; Zhang, Ye; Hu, Chunfang; Liu, Wenchao; Lu, Haizhen (Frontiers in Oncology, 2021)
Background Despite Adenoid cystic carcinoma (ACC) with cribriform or tubular components being recognized as a potentially indolent malignancy, ACC displaying solid or, more rarely, high-grade transformation (HGT) components is considered a more aggressive variant of the disease. As it is difficult to measure the proportion of the solid component objectively, and the role of HGT in the current grading system remains unclear, the prognostic influence of tumor grading remains controversial. In addition, postoperative radiotherapy (PORT) has been proven to be effective in local control of ACC of the head and neck (ACCHN) with a high rate of nerve invasion and close surgical margin. However it remains to be explored that whether PORT could improve the survival of patients with ACC, particularly those with HGT. Methods A series of 73 surgically treated primary ACCHN cases were retrospectively accessed. Immunohistochemical staining was performed to observe the biphasic ductal-myoepithelial differentiation and to identify the HGT components of ACC for tumor grading. The correlation between tumor grading and clinicopathological characteristics was analyzed. Univariate and multivariate prognostic analysis were performed for progression-free survival (PFS) and overall survival (OS). Results Of the 73 included cases, 47 were grade I-II ACC and 26 were grade III ACC. Among the grade III cases, 14 with loss of biphasic ductal-myoepithelial differentiation identified by immunostaining were classified as HGT, and could be distinguished from conventional grade III cases. These HGT cases were correlated with a high propensity of lymph node metastases and more advanced stage. Univariate analysis demonstrated that tumor grading, perineural invasion, T stage, stage groups, and PORT were predictors for PFS, whereas tumor grading, margin status, and PORT were predictors for OS. However, only tumor grading and PORT were independent predictors for PFS and OS. The patients with HGT had significantly worse prognosis than those with conventional ACC. Moreover, disease progression tended to occur more frequently in younger patients. Among the patients with HGT, those who received PORT had a longer median survival time than those who did not. Conclusion HGT ACC identified by loss of biphasic differentiation should be considered in tumor grading. Tumor grading and PORT were independent predictors for disease progression and OS in surgically treated ACCHN patients.